2000
DOI: 10.1200/jco.2000.18.15.2798
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic Acid Receptor-Beta as a Prognostic Indicator in Stage I Non–Small-Cell Lung Cancer

Abstract: Unexpectedly, strong RAR-beta expression was associated with a significantly worse outcome of early-stage NSCLC. The mechanisms underlying this clinically and biologically important finding should be further explored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(62 citation statements)
references
References 26 publications
4
56
2
Order By: Relevance
“…COX-2, a marker of poor prognosis in stage I NSCLC, also is a promising target in treating NSCLC (34). Inhibition of COX-2 by selective COX-2 inhibitors enhances the response to chemotherapeutic regimens and leads to a prolonged progression-free survival when used in combination with radiotherapy (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…COX-2, a marker of poor prognosis in stage I NSCLC, also is a promising target in treating NSCLC (34). Inhibition of COX-2 by selective COX-2 inhibitors enhances the response to chemotherapeutic regimens and leads to a prolonged progression-free survival when used in combination with radiotherapy (35,36).…”
Section: Discussionmentioning
confidence: 99%
“…In situ hybridization A previously described method of nonradioactive in situ hybridization was used for detection of COX-2 expression (Khuri et al, 2001;Kong et al, 2005). The stained sections were reviewed in a manner similar to immunohistochemistry.…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…2 Although RAR-β is effectively upregulated by 9cRA in bronchial epithelium, data implicating maintenance of RAR-β intratumorly in NSCLC patients showed a poorer prognosis have cast RAR-β in a less favorable light. 1,3 Retinoid refractoriness, in terms of inducing RAR-β expression or apoptosis with treatment of retinoids, is attributable, at least partially, to aberrant promoter methylation and histone H3 acetylation. One study showed retinoid receptor function to be intact in the t-RA-refractory malignant HBE cell line, however, suggesting that the defect in retinoid signaling in this lung carcinogenesis model was not intrinsic to the retinoid receptors.…”
Section: Introductionmentioning
confidence: 99%